Highly and Broad-Spectrum In Vitro Antitumor Active cis-Dichloridoplatinum(II) Complexes with 7-Azaindoles - Štarha, Pavel; Dvořák, Zdeněk; Trávníček, Zdeněk (PLOS ONE, 2015)
The cis-[PtCl2(naza)2] complexes (1–3) containing monosubstituted 7-azaindole halogeno-derivatives (naza), showed significantly higher activity than cisplatin towards ovarian carcinoma A2780, its cisplatin-resistant variant A2780R, osteosarcoma HOS, breast carcinoma MCF7 and cervix carcinoma HeLa cell lines, with the IC50 values of 3.8, 3.5, 4.5, 2.7, and 9.2 μM, respectively, obtained for the most active complex 3. As for 4 and 5 having disubstituted 7-azaindoles in their molecule, the significant cytotoxicity was detected only for 4 against A2780 (IC50 = 4.8 μM), A2780R (IC50 = 3.8 μM) and HOS (IC50 = 4.3 μM), while 5 was evaluated as having only moderate antiproliferative effect against the mentioned cancer cell lines with IC50 = 33.4, 24.7 and 46.7 μM, respectively. All the studied complexes 1–5 effectively avoided the acquired resistance of ovarian carcinoma cell line. On the other hand, the complexes did not reveal any inhibition activity on the purified 20S proteasome from the A2780 cells. The representative complexes 3 and 5 showed low ability to be hydrolysed, but their stability was markedly lowered in the presence of physiological sulphur-containing biomolecule glutathione (GSH), as proved by the 1H NMR spectroscopy and mass spectrometry studies. A rate of interaction of the studied complexes with GSH was affected by an addition of another mechanistically relevant biomolecule guanosine monophosphate. The differences in interactions of 3 and 5 with GSH correlate well with their different cytotoxicity profiles.